In commemoration of professor V.P. Karpov - Semyonova L.S. (Medičnì Perspektivi)
This article is about professor Karpov V.P., a prominent scientist, first rector of Yekaterinoslav Medical Academy. Biography of a great investigator, his main achievements in the area of histology, biology, theory and history of medicine was studied. Professor Karpov V.P. always combined his great scientific, organizational and research work with social activity. Monographs of professor Karpov V.P. and conferences organized by him were of great importance in the solution of such new problems as theary of microscope and cell amitosis. Professor Karpov is a founder of a large school of histology. Thanks to his active participation and personal guidance, in 1917 department of histology was founded in Yekaterinoslav Medical Institute. The author of the article has analyzed Hippocrates` works translated into Russian by professor Karpov V.P. and pointed out their significance for modern medical science and practice.